(untitled) (Revista Científica Integrada, 2024)
Objective: to evaluate the scientific literature on labiaplasty, considering the impact of this intervention on the clinical and psychological aspects of women. Methods: A scoping review was performed using the MEDLINE/Pubmed, Scopus and Web of Science databases, by crossing the keywords/descriptors: “Intimate surgery”, “Aesthetic procedures” and “Labiaplasty”, crossed with the Boolean operator AND or OR. The inclusion criteria were defined as: articles published in the last 10 years, which addressed the risks and/or benefits of labiaplasty, and/or the degree of satisfaction of women after labiaplasty. Only original/primary articles were considered for inclusion. Results: A total of 360 studies were identified, of which eight met the eligibility criteria, including prospective, experimental, retrospective, documentary, cross-sectional and qualitative studies published between 2015 and 2024. No relevant studies were found in the gray literature. The analysis considered variables such as postoperative complications, aesthetic and functional satisfaction, and psychological impacts. The complication rate varied, with the most common being complete dehiscence and hematomas. Regarding postoperative satisfaction, most women reported satisfactory aesthetic and functional results, with improvements in self-esteem, sexual function, and body image. However, patients with greater preoperative psychological distress were less satisfied with the surgical results. Conclusion: Labiaplasty was considered a safe procedure, with a low incidence of serious complications, but it requires strict monitoring to minimize complications. The literature emphasizes the need for multidisciplinary approaches in the care of these patients, considering the physical, emotional, and social aspects involved, and for more research on the subject.